Peningkatan Kemampuan Keterampilan Komputer dan Pengelolaan Informasi Dalam Mendukung Gerakan Literasi Digital Pada SMKN 1 Sakra - Bahtiar Imran; Zaenudin (Yayasan Literasi Sains Indonesia, 2022)
Skills in using computers or digital are also very instrumental in determining a person's success in this case at the level of education. Vocational High School (SMKN) 1 Sakra is a vocational high school in Sakra District, East Lombok district. Class of 2020 students are students who from the beginning of entry to graduation are students who created the Covid 19 pandemic, the teaching and learning process uses courage. Vocational students who should get maximum practicum are constrained because learning is carried out at home using bold learning, this causes the knowledge and skills of grade 3 students to be minimal and can result in students having difficulty finding work. From this problem, the PkM team at the Mataram University of Technology improved computer skills and information management by conducting training that focused on the introduction of the internet, operating MS. Office and how to manage information in this case using Google Drive. The results of this study were students' knowledge of computers and information technology, students were able to operate well Ms. Office and students are able to manage information well.